Performance, Stability Analysis, and Selection for New Yellow-Fleshed Sweet Potato (Ipomoea batatas [L.] Lam.) in West Java, Indonesia - Yohanis Amos Mustamu; Debby Ustari; Arif Affan Wicaksono; Vergel Concibido; Tarkus Suganda; Agung Karuniawan (International Journal of Agronomy)
Genotype–environment interaction (GEI) information is essential in plant breeding programs. The objectives of this study were to select high-yielding and stable yellow-fleshed sweet potato (YFSP) genotypes in different environments and identify the favorable environment for testing. The trials were conducted in four different locations in West Java, Indonesia, using randomized complete block design (RCBD) with three replications. The results showed that yield was the primary source of variation, accounting for 46.947% of the total variation, followed by GE effect (29.938%) and genotype (23.115%). Additive Main Effect and Multiplicative Interaction (AMMI) Stability Value (ASV) analysis showed Prai (838) and high-yielding KMDR were the genotypes with the most stability performance in all environments. Parametric and nonparametric stability analysis showed that Prai (838) produced high yields with stability performance in all environments. AMMI showed that Prai (838) and 264 were stable in all environments. Genotype + genotype by environment (GGE) biplot analysis identified Prai (838), 8(11), and Rancing, of which 8(11) and Rancing were the best performing vertex genotypes in Jatinangor. Prai (838) was the stable genotype in all stability analyses used. AC Putih was categorized as having a high level of stability (73.663%) according to coefficient of variability (CVi) with the sustainability index (SI) ranked first. Stable genotypes can be recommended as new genotypes, while Jatinangor can be used in favorable environment for testing.